Jokowi's Opinions and Attitudes towards Covid-19 in Indonesia: A Critical Discourse Analysis - Yasin, Hasnan; Hidayat, Didin Nuruddin; Alek, Alek (Center of Language and Cultural Studies [CLCS], 2021)
This study aims to investigate the discourse structure, social cognition, and social context of Jokowi’s speech about Covid-19 which partly represents Jokowi’s opinion and attitudes towards Covid-19 in Indonesia. The method used is qualitative research that employs critical discourse analysis (CDA) as its design of analysis. The CDA used in this research focuses on Van Dijk concept. The data collected was from the video of his speech entitled Pandemi: Fakta dan Data, Bukan Kira-Kira on Presiden Joko Widodo YouTube channel and then transcribed into texts. The results show that Jokowi’s speech about Covid-19 presents all elements of the discourse analysis concept proposed by Van Dijk including text structure, social cognitive, and social analysis. The speech focuses on the perspective of Jokowi about Covid-19. The strength, the power, and the purposes of Jokowi can be shown from the languages used. They can truly be felt, expressly seen, and well understood.